Reflections on the Great Immigration Battle of 2006 and the Future of the Americas - Jonas, Susanne (Social justice, 2006)
Part of a special issue on immigration rights and national insecurity. The writer examines possible future reverberations in the U.S. of the great immigration battle of 2006. The peaceful uprising of undocumented migrants was triggered by anti-immigrant politicians seeking to pass a bill that would criminalize undocumented immigrants. It was, however, the culmination of a whole decade of unprecedented abuse and punishment of legal and illegal immigrants. In order to prevent the border security first" campaign from succeeding, ongoing mobilizations by immigrants and their supporters will be necessary to highlight the message that immigrants are not criminals but human beings endowed with inalienable rights that they carry with them as they cross borders.